Marketing Strategy and Customer Relationship Management in Lighting Manufacturing Companies in Fujian Province, China - Chen, Junyu (International Journal of Global Economics and Management, 2024)
This study aimed to provide strategic guidance to stakeholders of lighting companies in Fujian Province, to enhance the competitiveness of local lighting companies in the midst of complex market dynamics and technological advancements, and to propose innovative solutions for long-term growth and sustainable development. Through in-depth research, this paper reveals the effectiveness of Fujian Province lighting firms in terms of marketing strategy and customer relationship management, as well as the significant links between these two key factors. Specifically, the study evaluates in detail the performance of marketing strategy and customer relationship management practices across various dimensions. Marketing strategy practices were explored in terms of product, price, channel, and promotion; while customer relationship management was described in terms of customer value, customer satisfaction, and customer retention. In addition, three hundred respondents were selected for this study with the support of Fujian Optoelectronics Industry Association and the corresponding questionnaires were successfully collected. Through the analysis of statistical tools, the study found that there is a strong link between marketing strategies and customer relationship management practices. The study also found that in the subgroup analysis based on gender, age, years of experience, and type of business entity, males, 36 to 40 years of age, and those with 3 to 4 years of experience rated the relationship between marketing strategy and CRM practices higher. Based on these findings, the researchers proposed an action plan to improve the marketing strategy practices and CRM practices of lighting firms in Fujian Province to ensure that these practices are more effective and responsive to market needs. This will not only enhance the competitiveness of Fujian lighting companies, but also lay a solid foundation for their sustainable success in the future.